Development of Vegetable Based Cropping Pattern In Cumilla Region (Bangladesh Agronomy Journal, 2020)
A field experiment was conducted at MLT site, Chandina under on-farm research division (OFRD), Bangladesh Agricultural Research Institute, Cumilla during 2015-16 and 2016-17 to study an economically profitable vegetable based cropping pattern in Cumilla region for increasing cropping intensity and productivity as well as to meet the vegetable demand for farm family as well as the country. The studied vegetable based cropping patterns were CP1: Red amaranth-Potato-Coriander-Indian Spinach-Ladies finger-Cauliflower and CP2: Red amaranth-Potato-Indian spinach-Ladies finger-Coriander-Red amaranth, respectively. The results showed that six vegetable crops could be grown successfully one after another in a sequence in the farmer’s field instead of two or three crops based pattern in a piece of land. From the research results it was revealed that the highest Potato equivalent yield (PEY) 226.66 t ha-1 was obtained from cropping pattern CP1: Red amaranth-Potato-Coriander-Indian Spinach-Ladies finger-Cauliflower where the lower PEY (171.38 t ha-1) in CP2: Red amaranth-Potato-Indian spinach-Ladies finger-Coriander-Red amaranth cropping pattern. From the economic analysis, it was observed that the highest gross return Tk. 22,66,600 ha-1 was obtained from cropping pattern CP1: Red amaranth-Potato-Coriander-Indian Spinach-Ladies finger-Cauliflower which leads to the highest gross margin (Tk. 18,94,542 ha-1) as well as the highest BCR (6.09) from that cropping pattern compared to CP2.Bangladesh Agron. J. 2019, 22(1): 7-13